The Effect of Seaweed Addition on the Organoleptic Properties of Tempeh Sausages - Dian Estiningtyas; Berliana Puspita (Jurnal Gizi Prima (Prime Nutrition Journal), 2024)
Background: Food production today not only caters to consumer preferences but also must consider nutritional and health aspects. Sausages available on the market are typically made from meat, which is low in fiber and high in cholesterol, posing risks for atherosclerosis and other degenerative diseases. Tempeh and seaweed are local food ingredients rich in nutrients that can serve as alternative materials for innovating healthy sausage products.Research Methods: This study employed a complete randomized design (CRD) experimental method with one factor: seaweed substitution at three levels—5%, 10%, and 15% of the weight of tempeh. A sensory evaluation was conducted using the hedonic method, and the data were analyzed with one-way ANOVA.Research Result: The evaluation of color, texture, and aroma showed scores ranging from 1.80 to 2.10 on a neutral scale. The taste evaluation resulted in scores ranging from 1.80 to 2.00 on the neutral scale, with statistical analysis revealing a significant effect of seaweed addition on the taste of tempeh sausages (p<0.05).Conclusion: Indicates that the addition of seaweed does not significantly affect the color, aroma, and texture of tempeh sausages (p>0.05) but has a significant impact on taste (p<0.05). The sensory evaluation results showed that the color scores for tempeh sausages ranged from 1.90 to 2.10 (neutral), the aroma scores ranged from 1.63 to 1.97 (neutral), the taste scores ranged from 1.80 to 2.00 (neutral), and the texture scores ranged from 1.83 to 2.00 (neutral).